Eficacia de las medidas cautelares en el procedimiento sancionador como salvaguarda de la seguridad alimentaria en el Centro Histórico de Quito. - Sánchez Sevillano, Wellington Andrés (2024)
This work aims to evaluate the effectiveness of precautionary measures in the administrative sanctioning procedure as a safeguard for food safety in the Historic Center of Quito in the year 2023. To this end, a descriptive explanatory methodology was used as a diagnostic approach to the commercialization of food in this part of the municipality to identify the precautionary measures imposed by the Metropolitan Control Agency as the competent authority, and from there, to identify in detail their effectiveness in the sanctioning procedure to safeguard food safety. This analytical exercise was oriented from the quantitative research approach, starting from the observation of the specific situation to reach general conclusions. Therefore, qualitative techniques such as interviews and direct observation and quantitative techniques such as surveys were used for data collection. This means that the collection tools used were the list of structured questions, the field diary, and the questionnaires. Among the results, it was corroborated that there is little effectiveness of the precautionary measures implemented in the administrative sanctioning procedures. Although these measures show the full extent of the sanctioning power of the competent authority to prevent practices that endanger food safety in the Historic Center of Quito, the fact is that this does not stop merchants from continuing these practices in the public space. This is because, for many, it is the only means of livelihood and citizens will not stop consuming them either.